Digital Conversation Analysis on Screen-Captured Data: Comparing Instagram Online Discourse on Smartphone vs Laptop - Latief, Muhammad Ridha Anugrah; Jumari, Rahmat; Ardiansya, Ariyanto; Lauren, Cendy; Derin, Tatum (Universitas Lancang Kuning, 2024)
The study of online discourse on social networking sites (SNSs) is a relatively recent field of study where most of the methodology to study online conversations has been derived from spoken conversation analysis (CA). This study attempts to contribute to the development of digital conversation analysis by analysing screen-captured data of publicly available online conversations on Instagram on April 2020. 186 screen-captured data are analysed with digital conversation analysis to discuss and compare the turn-taking, repair, action formation, action sequencing and the role of technology on the production of online conversations. Results show tentative proof that the screen-capture method of data collection has a unique strength in that it gives researchers insight onto the moment-by-moment production of the online conversation that is not available from the traditional method of transcribing. The novelty of this digital CA research is the comparison between smartphone- and laptop-version of screen-captured data, specifically how the different medium affects the production of online discourse of the same SNS.